2008
DOI: 10.1029/2006wr005568
|View full text |Cite
|
Sign up to set email alerts
|

Estimating plume degradation rates in aquifers: Effect of propagating measurement and methodological errors

Abstract: [1] Field estimates of plume degradation rates l [T À1 ] in aquifers provide a basis for assessing the possible impact of (toxic) organic pollutants on downstream environments; however, difficulties with measurement and methodology mean that estimated site-specific rates potentially involve considerable uncertainty. Here, we specifically show that if mass flow or average concentration measurements are associated with errors of $20% (or even less), the errors may in many cases propagate, magnify, and cause orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The interval may widen significantly if also the attenuation rate λ is variable, and depending on its possible cross-correlation with the advective travel time T [e.g., 34,[64][65][66]. Further investigations and realistic quantifications are needed for the spatial variability of biogeochemical attenuation rates and their correlation with the physics of flow and transport in both the surface water and not least the groundwater systems of hydrological catchments.…”
Section: Resultsmentioning
confidence: 98%
“…The interval may widen significantly if also the attenuation rate λ is variable, and depending on its possible cross-correlation with the advective travel time T [e.g., 34,[64][65][66]. Further investigations and realistic quantifications are needed for the spatial variability of biogeochemical attenuation rates and their correlation with the physics of flow and transport in both the surface water and not least the groundwater systems of hydrological catchments.…”
Section: Resultsmentioning
confidence: 98%
“…Malmström et al, 2004Malmström et al, , 2008Darracq and Destouni, 2007;Cunningham and Fadel, 2007;Jardine, 2008) -the errors of mass transport measurements implied by the chosen measurement methods and the coverage gaps between the chosen measurement points in time and space (e.g. Hannerz and Destouni, 2006;Beven, 2006;Jarsjö and Bayer-Raich, 2008;Destouni et al, 2008) -the chosen model resolutions and possible neglect of potentially important contributing mass transport processes at different scales (e.g. Lindgren and Destouni, 2004;Refsgaard et al, 2006;Destouni et al, 2006;Ganoulis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Jarsjö and Bayer‐Raich [2008] showed that the relative errors ɛ c in C av due to neglecting λ (assuming λ = 0 in degrading plumes) remain small for small capture zones ( r c ( t ) < 10 m) considering a degradation value range of δ = λ / u 0,w that has been observed in the field. For larger capture zones, the error may increase and the assumption λ = 0 can (under some conditions [ Jarsjö and Bayer‐Raich , 2008]) result in overestimation of C av . For instance, for values of κ = λr c ( t )/ u 0, w < 2, relative errors in C av remain within ɛ c < 1, while, e.g., κ > 3 yield relative errors ɛ c > 2.5.…”
Section: Inverse Problem For Homogeneous Aquifers: General Formulatiomentioning
confidence: 84%
“…The inverse solutions demonstrate that for relatively short pumping tests, where t ≪ RQn e /( bq 0, w 2 ), estimated C av values (given a measured C p ( t )) are not very sensitive to plume degradation (i.e., accurate C av estimates will be obtained, even if λ = 0 is assumed for degrading plumes), as long as κ = λr c ( t )/ u 0, w < 2. For higher values of κ, C av will generally be overestimated, if plume degradation is neglected; however λ can in such cases be determined independently in situ using multiple control planes [see Bayer‐Raich et al , 2006; Jarsjö and Bayer‐Raich , 2008].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation